Neurotransmitters: promising immune modulators in the tumor microenvironment - Xiao, Luxi; Li, Xunjun; Fang, Chuanfa; Yu, Jiang; Chen, Tao (Frontiers in Immunology, 2023)
The tumor microenvironment (TME) is modified by its cellular or acellular components throughout the whole period of tumor development. The dynamic modulation can reprogram tumor initiation, growth, invasion, metastasis, and response to therapies. Hence, the focus of cancer research and intervention has gradually shifted to TME components and their interactions. Accumulated evidence indicates neural and immune factors play a distinct role in modulating TME synergistically. Among the complicated interactions, neurotransmitters, the traditional neural regulators, mediate some crucial regulatory functions. Nevertheless, knowledge of the exact mechanisms is still scarce. Meanwhile, therapies targeting the TME remain unsatisfactory. It holds a great prospect to reveal the molecular mechanism by which the interplay between the nervous and immune systems regulate cancer progression for laying a vivid landscape of tumor development and improving clinical treatment.